Conservación de las raíces frescas de la yuca (Manihot esculenta Crantz) aplicándole el proceso de parafinado - Sotelo Contreras, Rosario; Acevedo Ampié, Guillermo (Nexo Revista Científica, 2012)
A characteristic of cassava root (Manihot esculenta Crantz) is the fast deterioration that occurs after harvesting, this process is called “Physiological Deterioration of Postharvest” (PDP). This study was made to determine the effect of waxing process in the conservation of the quality of the cassava root of cassava. This includes morphological quality, physiological quality, culinary quality and microbial deterioration. The study tested the conservation of roots from different places at different periods of time using waxing technology at low cost. During twenty one days of study for each lot submitted for technology, show good levels of conservation of their characteristics physiological and culinary. The results lead us to consider waxing technology of cassava producers to increase the periods of commercialization. Keywords: physiological deterioration post-harvest, morphological quality, culinary quality, microbial deterioration, physiological quality.